2016
DOI: 10.1002/cbdv.201500151
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antimicrobial and Cytotoxic Activity of Heracleum verticillatum Pančić and H. ternatum Velen. (Apiaceae) Essential Oils

Abstract: In this work, the chemical composition, antimicrobial and cytotoxic activity of Heracleum verticillatum Pančić and H. ternatum Velen. root, leaf, and fruit essential oils were investigated. The composition was analyzed by GC and GC/MS. Heracleum verticillatum and H. ternatum root oils were dominated by monoterpenes, mostly β-pinene (23.5% and 47.3%, respectively). Heracleum verticillatum leaf oil was characterized by monoterpenes, mainly limonene (20.3%), and sesquiterpenes, mostly (E)-caryophyllene (19.1%), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…48,49 Several investigations on other genus such as Heracleum also showed that octyl conjugated of butyric, acetic, and octanoic acids constitute the main SCFAE in essential oils of Heracleum genus. [50][51][52][53][54] This similarity in major SCFAE of both genus may reflect the pervious viewpoint about Tordylieae tribe of Apiaceae which also showed close phylogenetic characters. 55,56…”
Section: Pharmaceutical Sciences June 2019 25(2) 138-144 | 141mentioning
confidence: 56%
“…48,49 Several investigations on other genus such as Heracleum also showed that octyl conjugated of butyric, acetic, and octanoic acids constitute the main SCFAE in essential oils of Heracleum genus. [50][51][52][53][54] This similarity in major SCFAE of both genus may reflect the pervious viewpoint about Tordylieae tribe of Apiaceae which also showed close phylogenetic characters. 55,56…”
Section: Pharmaceutical Sciences June 2019 25(2) 138-144 | 141mentioning
confidence: 56%
“…pollinianum and H. orphanidis root, leaf and fruit oils exhibited antimicrobial activity that was in some cases stronger than the activity of reference antibiotics. 39,45 Additionally, H. orphanidis aerial parts oil exhibited prominent antibacterial activity, and moreover, it inhibited P. aeruginosa PAO1 biofilm formation and synthesis of toxic pyocyanin, as well as reduced its twitching and flagella mobility. 51 The cytotoxic activity of the analyzed H. sphondylium, H. sibiricum and H. montanum root, leaf, flower and fruit essential oils was tested against the cell lines of common cancer types, i.e.…”
Section: Bioactivity Of Essential Oilsmentioning
confidence: 98%
“…39,45 In the oil isolated by the microdissection of the vittae of H. sphondylium fruits collected in Italy in different development stages, the main components were also octyl acetate (18.1-34.6%) and octyl hexanoate (24.5-30.5%). Besides aliphatic esters, this oil contained the notable quantity of furanocoumarins, mostly analyzed HSPH oil in which only the trace of bergapten was identified.…”
Section: Chemical Composition Of Essential Oilsmentioning
confidence: 99%
“…For the purpose of our research, the plants were collected in Southeastern Europe (Serbia, Montenegro, North Macedonia and Slovenia), however, most of them are also native in some other parts of Europe, except H. verticillatum and H. orphanidis, which are endemic species of central Balkan (4,5). In previous researches, we analyzed the chemical composition of essential oils of different organs of these plants by GC-FID and GC-MS, and demonstrated their antimicrobial, cytotoxic (selective to cancer cell lines) and/or antioxidant activities (6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%